Early warning indicators of population collapse in a seasonal environment. Issue 6 (29th March 2021) - Burant, Joseph B.; Park, Candace; Betini, Gustavo S.; Norris, D. Ryan
Abstract: Recent studies have demonstrated that generic statistical signals derived from time series of population abundance and fitness‐related traits of individuals can provide reliable indicators of impending shifts in population dynamics. However, how the seasonal timing of environmental stressors influences these early warning indicators is not well understood. The goal of this study was to experimentally assess whether the timing of stressors influences the production, detection and sensitivity of abundance‐ and trait‐based early warning indicators derived from declining populations. In a multi‐generation, season‐specific habitat loss experiment, we exposed replicate populations of Drosophila melanogaster to one of two rates of chronic habitat loss (10% or 20% per generation) in either the breeding or the non‐breeding period. We counted population abundance at the beginning of each season, and measured body mass and activity levels in a sample of individuals at the end of each generation. When habitat was lost during the breeding period, declining populations produced signals consistent with those documented in previous studies. Inclusion of trait‐based indicators generally improved the detection of impending population collapse. However, when habitat was lost during the non‐breeding period, the predictive capacity of these indicators was comparatively diminished. Our results have important implications for interpreting signals in the wild because they suggest that the production and detection of early warning indicators depends on the season in which stressors occur, and that this is likely related to the capacity of populations to respond numerically the following season. Abstract : Seasonal laboratory populations of fruit flies were exposed to habitat loss in either the breeding or non‐breeding period. By measuring changes in abundance and traits, the authors showed that the seasonal timing of environmental stressors influences the detectability of early warning signals preceding tipping points from stable dynamics to collapse.